The Role and Regulation of Natural Killer (NK) Cells in Chemotherapy: A Literature Review - Pauzan, Pauzan (Jurnal Biologi Tropis, 2025)
Natural Killer (NK) cells, as innate immune effectors capable of targeting tumor cells without prior sensitization, interact complexly with chemotherapy, which can both enhance and suppress their functions. This literature review aims to comprehensively evaluate the role and regulation of NK cells in the context of chemotherapy over the past decade. Literature searches were conducted through Google Scholar, PubMed, Scopus, and Web of Science databases using relevant keywords. The review findings indicate that several chemotherapeutic agents can enhance NK cell activity by increasing the expression of activating ligands on tumor cells and promoting the release of pro-inflammatory cytokines. However, chemotherapy may also suppress NK cell function through systemic immunosuppression and alterations in the tumor microenvironment. NK cell-based immunotherapy, especially when combined with chemotherapy, demonstrates promising therapeutic potential. Recent studies support the development of strategies such as genetic modification, exogenous cytokine administration, and NK cell engineering to improve therapeutic efficacy. This review underscores the importance of further research to optimize the synergy between NK cells and chemotherapy in cancer treatment.